Railway Wheel Detector in the Presence of Eddy Current Brakes - Zamani, A.; Mirabadi, A. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, electromagnetic sensor is considered as a train wheel detector, which is one of the most important signalling systems to determine the clearance or occupancy of a track section. The wheel detector is affected by eddy current brakes and this problem has limited its use. In order to improve the wheel detection accuracy and eliminate the eddy current brake effect, the optimal design of sensors is carried out by means of finite element method. Kriging method is utilized to reduce the computational costs. Additionally, genetic algorithm is used as a multiobjective optimization method to find the optimum orientation.